Argonaute2 cleaves the anti-guide strand of siRNA during RISC activation. - Rand, T.A.; Petersen, S.; Du, F.; Wang, X. (Cell, 2005)
The mRNA-cleavage step of RNA interference is mediated by an endonuclease, Argonaute2 (Ago2), within the RNA-induced silencing complex (RISC). Ago2 uses one strand of the small interfering (si) RNA duplex as a guide to find messenger RNAs containing complementary sequences and cleaves the phosphodiester backbone at a specific site measured from the guide strand's 5' end. Here, we show that both strands of siRNA get loaded onto Ago2 protein in Drosophila S2 cell extracts. The anti-guide strand behaves as a RISC substrate and is cleaved by Ago2. This cleavage event is important for the removal of the anti-guide strand from Ago2 protein and activation of RISC.